Two Entomophagous Isolated From Sumatera Utara; Potential As Biocontrol Agent Againts Nematode - Hastuti, Liana Dwi Sri; Nicklin, Jane; Siregar, Ameilia Zuliyanti (Jurnal Online Pertanian Tropik, 2019)
Two species of nematophagous fungi has been isolated from Sumatera Utara soil, with an aim of harnessing their potential in the biological control of plant parasitic nematodes or animal parasitic nematodes in Indonesia, especially in Sumatera Utara. Soil samples were collected from tobacco plantations, vegetable fields and ornamental plantings in the Berastagi area, and also from livestock in local farms and a dairy farm in Berastagi Area, Karo Regency. Soil also collected from un-cultivated area in Sibolangit National Park, Karo Regency. The pour method described by Larsen (1998) and the sprinkle method described by Jafee et al. (1996) were used to isolate the nematophagous fungi from soil. In this study the Chloramphenicol Water Agar Media has been used as culture media and Ceanorhabditis elegans has been used as bait. Two nematophagous fungi known as insect pathogens (entomophagous) have been isolated and determined as Lecanicillium lecanii and Paecilomyces fumosoroseus